The qualities, values, skills and strategies of successful primary school leaders: case studies of two primary school head teachers in Lagos, Nigeria - Felix-Otuorimuo, Ireremena (2019)
This study assesses the qualities, values, skills and strategies of two successful primary school Head Teachers in Lagos, Nigeria. It explores the challenges facing Nigerian primary school leadership in both public and private schools and discusses the literature on successful international and Nigerian school leadership. It investigates the interpretations of the Head Teachers’ perceptions of success and their successful strategies and practices that impact on teachers’ working conditions and student outcomes. The research on successful school leadership has been considered across cultural and national boundaries to reveal the diverse outcomes, which can impact on the topic. Studies on successful leadership have been carried out with the regards to the ability of primary school Head Teachers to influence the internal members, students, teachers, parents and board members, as well as other administrative staff members. The influence of Head Teachers can impact on the entire school community either directly or indirectly in terms of socio-academic and moral success, including the external community, as well impacting on education districts and on local and national policymakers. This multi-perspective case study has adopted an explanatory approach to identify and describe the two Head Teachers’ actions, qualities, educational values, skills and successful strategies. The two Head Teachers impacted on teachers’ working conditions and students’ moral and socio-academic performance in challenging contexts. This study examines the means of combining multiple leadership dimensions to overcome the specific challenges that the Head Teachers were experiencing. These Head Teachers had no formal knowledge of how to combine current leadership concepts to achieve school improvement. The educational values and experiences of the Head Teachers influenced the ways in which they achieved success in their schools. The findings reveal that successful primary school leadership in Nigeria is a collective and direct effort of the entire school community working together as a family unit, which cuts across the cultural and national boundaries of sub-Saharan Africa. The personal visions of the Head Teachers to lead their schools to succeed through their spirituality, personal care and relational trust systems of other school members created a symbiotic relationship between the home and the school, a collaborative atmosphere that ensured teachers’ pedagogic skills were regularly updated, which impacted on improvement for the whole school.